ChemInform Abstract: Synthesis and Structures of Type‐I Clathrates: Rb6Na2Ge44.89(1), Cs6Na2Zn4Ge42 and Cs6.40(1)Na1.60(1)Ga8Ge38. Issue 45 (October 2016) - Zhang, Hui; Mu, Gang; Huang, Fuqiang; Xie, Xiaoming
Abstract: Rb6 Na2 Ge44.89, Cs6 Na2 Zn4 Ge42, and Cs6.40 Na1.60 Ga8 Ge38 are prepared by solid state reaction of the elements in stoichiometric proportions (Ta container in evacuated quartz ampoules, 650 °C, 1—2 weeks).